31.4k views
3 votes
What is the inverse of the function h(x)=\dfrac{3}{2}(x-11)h(x)=

2
3

(x−11)h, left parenthesis, x, right parenthesis, equals, start fraction, 3, divided by, 2, end fraction, left parenthesis, x, minus, 11, right parenthesis?
h^{-1}(x)=h
−1
(x)=h, start superscript, minus, 1, end superscript, left parenthesis, x, right parenthesis, equals

1 Answer

5 votes

Answer:


\boxed{\red{\sf h^(-1)(x)=(4)/(3)x+22}}

Explanation:

Given :-

  • h(x) = 3/2 ( x - 11)

And we need to find the Inverse of the function . So for that firstly replace h(x) with y , we have ,


:\implies h(x) = 3/2 ( x -11)


:\implies y = 3/2 ( x - 11)


:\implies y = 3/2x - 33/2

  • Now replace x and y.


:\implies x = 3/2y - 33/2

  • Now solve out for y .


:\implies x + 33/2 = y × 3/2


:\implies y = (2x + 33)×2/3


:\implies y = 4x/3 + 22

  • Replacing y with h-¹(x)


:\implies h-¹(x) = 4x/3 + 22

Hence the inverse of the function is 4x/3 + 22

User Logcat
by
5.3k points